Revision of Epironastes Carne, 1957 (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini: Pseudoryctina) with description of the female, behaviours, and habitats - Hutchinson, Paul M.; Allsopp, Peter G. (Zootaxa, 2020)
The genus Epironastes Carne, 1957 (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini: Pseudoryctina) from southern Western Australia, Australia is revised. Teinogenys demarzi Endrődi, 1971 is transferred to Epironastes, becoming E. demarzi new combination and is redescribed. The female of E. abruptus Carne, 1957 is described. A female attributed to Epironastes nigrisetosus Carne, 1957 by Carne is re-assessed and is considered to be a female of Cavonus sculpturatus Blackburn, 1888. All four species, including E. limbatus Carne, 1957 and E. abruptus Carne, 1957, are redescribed. A key is given to identify males of all four species. New distributional records are presented, and behaviours and habits discussed.